Low Mastery of Accounting Basics in Diploma 3 Accounting Students of Politeknik Negeri Medan - Yulifati Laoli (Universitas 17 Agustus 1945, 2021)
This research aims to identify the causes of low mastery of the basics of accounting among Politeknik Negeri Medan Diploma 3 Accounting students. The method used is study documentation, utilizing secondary data sources such as student academic reports and teaching notes. The research results show that this low mastery is caused by students' limited analytical abilities, lack of learning support, and teaching methods that are less adaptive to students' needs. The recommendation given is to improve the quality of learning through curriculum revision and development of learning support programs for students.